Student Development Program Planning At SMP Islam Al-Ulum Terpadu Medan - Hasrian Rudi Setiawan (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to determine the planning of student development programs at SMP Islam Al-Ulum Terpadu Medan. Researchers used qualitative research methods with a phenomenological approach in this study. Data was collected using data collection techniques, namely: observation, interviews, and documentation studies. Data analysis was carried out using techniques: selecting, presenting data, and drawing conclusions. The results of this study stated that the planning of student development programs at SMP Islam Al-Ulum Terpadu Medan, the planning was carried out in the form of academic and non-academic programs. For student development programs, planning is carried out by determining achievement targets, human resources, facilities and infrastructure, how/techniques to do it, the costs required and when to implement them.